2001
DOI: 10.5271/sjweh.634
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related hospital utilization and mortality in different occupations in Sweden in 1991-1995

Abstract: Objectives This study investigated alcohol-related hospital utilization and alcohol-related mortality according to occupation among men and women. Whether increased rates of alcoholism in some occupations result from circumstances within the occupation or from selective recruitment of persons prone to alcohol misuse was studied.Methods All Swedish residents were included who reported an occupation in the censuses of 1985 and 1990 and were born in . The relationships between occupation and hospitalization du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
3
24
1
1
Order By: Relevance
“…High risk drinking was found to be more prevalent among upper managers (OR = 2.39, 95% CI = 1.07-5.34), middle managers (OR = 1.87, 95% CI = 1.05-3.32), semi-qualified white collar workers (OR = 1.71, 95% CI = 1.18-2.49), and qualified blue collar workers (OR = 2.11, 95% CI = 1.41-3.16) compared to non-qualified blue collar workers (Marchand, 2008). However, manual and unskilled workers were at greater risk of alcohol-related diagnoses than non-manual workers (Hemmingsson et al, 1998), skilled workers (Hemmingsson et al, 1997), and the study population overall (Hemmingsson and Ringback, 2001). In contrast to Marchand's (2008) findings, workers in lower status occupations were more at risk of alcohol use and dependence than workers in higher status occupations (Crum et al, 1995).…”
Section: Structural and Socio-economic Factorsmentioning
confidence: 69%
See 3 more Smart Citations
“…High risk drinking was found to be more prevalent among upper managers (OR = 2.39, 95% CI = 1.07-5.34), middle managers (OR = 1.87, 95% CI = 1.05-3.32), semi-qualified white collar workers (OR = 1.71, 95% CI = 1.18-2.49), and qualified blue collar workers (OR = 2.11, 95% CI = 1.41-3.16) compared to non-qualified blue collar workers (Marchand, 2008). However, manual and unskilled workers were at greater risk of alcohol-related diagnoses than non-manual workers (Hemmingsson et al, 1998), skilled workers (Hemmingsson et al, 1997), and the study population overall (Hemmingsson and Ringback, 2001). In contrast to Marchand's (2008) findings, workers in lower status occupations were more at risk of alcohol use and dependence than workers in higher status occupations (Crum et al, 1995).…”
Section: Structural and Socio-economic Factorsmentioning
confidence: 69%
“…However, one study found that females in male-dominated occupations had an increased relative risk of alcoholism diagnoses in comparison to the study population (Hemmingsson and Ringback, 2001). Another study found female managers had higher levels of alcohol problems, needed more alcohol to feel the effects or be intoxicated than male or female nonmanagers and male managers (p 6 .05) and were more likely to drink immediately after work (OR = 1.27, 95% CI = 1.01-1.60) (Moore et al, 2003).…”
Section: Demographic Factorsmentioning
confidence: 91%
See 2 more Smart Citations
“…Research on the prevalence of alcohol misuse among workers has found those employed manual occupations have higher rates of excessive drinking (Hemmingsson & Ringback Weitoft, 2001). In particular, farm workers and service industry employees have been found to have higher risk and those working in professional occupations lower risk (Jarman et al, 2007;Matano et al, 2002).…”
Section: Introductionmentioning
confidence: 99%